(untitled) (The Journal of Sindhuli Multiple Campus, 2026)
This study investigates the factors affecting financial literacy among youths in Koshi Province, Nepal. Quantitative cross-sectional survey design was used by collecting data from youths aged 18-40 years (n=144) using a structured questionnaire. Financial literacy was modeled as the dependent variable, while attitudes toward investing, actual investment behavior, risk tolerance, and preference for investment options specified as independent variables. Reliability analysis demonstrated strong internal consistency for most constructs (overall Cronbach’s alpha = .905). Descriptive statistics revealed moderate level of financial literacy, though the higher mean scores were on the conceptual items as opposed to regular and diversified practice of investment. The Pearson correlation coefficients indicated strong positive relationships between attitudes towards investing (r = .647, p =.001), actual investment behavior (r =.519, p=.001), risk tolerance (r =.406, p=.001) and the investment options preferences (r =.240, p=.004) with the financial literacy. The multiple regression analysis showed that, the attitudes toward investing (beta =.524, p <.001) and actual investment behavior (beta =.257, p =.001) were significant predictors of financial literacy, whereas risk tolerance and investment preferences did not predict financial literacy with significant values. The results have emphasized the critical role of the cognitive and behavioral elements in financial literacy and the importance of practice-based financial education aimed at young population groups in Koshi Province.